Range-wide genetic structure and demographic history in the bat ectoparasite Cimex adjunctus. Issue 1 (December 2016) - Talbot, Benoit; Vonhof, Maarten; Broders, Hugh; Fenton, Brock; Keyghobadi, Nusha
Abstract Background Evolutionary histories of parasite and host populations are intimately linked such that their spatial genetic structures may be correlated. While these processes have been relatively well studied in specialist parasites and their hosts, less is known about the ecological and evolutionary consequences of relationships between generalist ectoparasites and their hosts. The aim of this study was to investigate the genetic structure and demographic history of a bat ectoparasite, Cimex adjunctus, whose host affinity is weak but the biology of the potential hosts have been well studied. This ectoparasite has been hypothesized to rely on its hosts for dispersal due to its low inherent dispersal potential. Here we describe genetic diversity and demographic history inC. adjunctus through most of its range in North America. We investigated variation at the cytochrome c oxidase 1 mitochondrial gene and nine microsatellite markers, and tested the prediction that genetic diversity inC. adjunctus is spatially structured. We also tested the prediction that demographic history inC. adjunctus is characterized by range and demographic expansion as a consequence of post-Pleistocene climate warming. Results We found stronger spatial structuring of genetic diversity inC. adjunctus than has been quantified in two of its hosts, but contrast in amount of variation explained by host association with different genetic markers (i.e., nuclear vs mitochondrial DNA). Also, C. adjunctus' history is not primarily characterized by demographic and range expansion, as is the case with two of its key hosts. Conclusions Our study shows different patterns of genetic structure and demographic history inC. adjunctus than have been detected in two of its key hosts. Our results suggest an effect of a loose parasite-host relationship and anti-parasitism strategies on genetic structure and post-Pleistocene recovery of population size.